Women's Struggle Against the Exploitation of Nature Dian Purnomo’s Novel A Study of Ecofeminism - Faridhatun Nikmah; Agus Nuryatin; Mulyono Mulyono (Universitas Negeri Semarang, 2024)
Currently, novels are not only used as a form of emptiness, but also as a form of representation of women's struggles. One of the novels that represents women's struggle is the novel Women Who Wait in the Passage to the Sea by Dian Purnomo. This novel tells the struggle of women's roles in preserving the natural environment on Sangihe Island from a gold mining company. The purpose of this study is to describe the form of women's open resistance against the exploitation of nature in the novel Women Who Wait in the Passage to the Sea by Dian Purnomo. The method used in this study is qualitative descriptive. The results of this study show that there is an open resistance carried out by women in fighting against the exploitation of nature. The open resistance found included forming an alliance organization to save Sangihe Island, resistance through legal channels, signing petitions of community rejection of mining, demonstrations at police stations and DPRD, struggle campaigns in waters, spreading news of mining rejection both at the national and international levels. It can be concluded that there is open resistance carried out by women as a form of preserving the natural environment on Sangihe Island for future generations.